Yogurt Berbasis Kecambah Kacang Tanah (Arachis hypogaea) dan Akar Alang-Alang (Imperata cylindrica) Kaya Antioksidan serta Nutrisi Esensial: Minuman Fungsional Dislipidemia: Peanuts (Arachis hypogaea) Sprout Plus Cogon grass (Imperata cylindrica) Roots Yoghurt Rich in Antioxidants and Essential Nutrients: A Dyslipidemic Functional Drink - Hery Winarsi; Gumintang Ratna Ramadhan; Yovita Puri Subardjo; Nur Indahsari; Fathiya Laeliya (Amerta Nutrition, 2026)
Background: Antioxidant-rich foods may help reduce oxidative stress associated with dyslipidemia. Objectives: This study evaluated the effects of peanut sprout milk–skim milk ratio, cogon grass (Imperata cylindrica) root concentration, and lactic acid bacteria (LAB), as well as their interactions, on the physicochemical and bioactive properties of PeaSco Go, a functional beverage intended for individuals with dyslipidemia. Methods: A factorial randomized block design was used with three factors: peanut sprout milk–skim milk ratio, cogon grass root concentration, and LAB level. Total phenolics were determined by the Folin–Ciocalteu method, vitamin C by iodometry, fiber by the gravimetric method, and soluble protein by the Lowry method. The best formulation was selected using the Effectiveness Index. Results: The milk ratio significantly increased total phenolics (p=0.004) but decreased vitamin C (p-value=0.004), soluble protein (p-value=0.002), and fiber (p-value=0.048). LAB significantly increased phenolics (p-value=0.001), vitamin C (p-value=0.029), soluble protein (p-value=0.008), and fiber (p-value=0.029). Cogon grass roots significantly increased fiber (p-value=0.032) and decreased soluble protein (p-value=0.036), with no significant effects on phenolics (p-value=0.883) or vitamin C (p-value=0.500). Significant interactions were found for vitamin C (p-value=0.001) and soluble protein (p-value=0.001), but not forphenolics (p-value=0.883) or fiber (p-value=0.550). The optimal formulation contained a 70:30 peanut sprout milk–skim milk ratio, 5% cogon grass roots, and 3% LAB, producing 1,009.57 mg GAE/L phenolics, 51.68% soluble protein, 93.27% vitamin C, and 1.47% fiber. Conclusions: PeaSco-Go shows potential as an antioxidant-rich functional beverage for improving lipid profiles in dyslipidemia.